A Portrait of English Student in Learning Approaches: A Case Study for Indonesia And Thai Student - Panuwat Hussanee; Febti Ismiatun (LET: Linguistics, Literature and English Teaching Journal)
This case study delves into the portrait of English language students from Indonesia and Thailand in their learning approaches. With the increasing importance of English as a global language. This has led to a shift in how students approach learning the language, particularly in non-English speaking countries, focusing on Indonesian and Thai students who study in the English Department of the Islamic University of Malang. The study seeks to understand how students in Indonesia and Thailand have transformed their learning approaches to adapt to the demands of their academic and social environments. To gather data, the study employed qualitative interviews and observations of students in their natural settings. The study found that students in Indonesia and Thailand have developed a range of innovative approaches to learning English that goes beyond traditional classroom methods. The results indicate that these students employ a combination of approaches, including the use of technology, peer learning, and self-directed learning. The students are also motivated and committed to learning the language, which is essential in developing their proficiency in English. The findings suggest that a combination of motivation, commitment, and experimentation with different strategies and techniques is necessary for effective language learning.